A cascade deprotonation/intramolecular aldol reaction of α-carbonyl sulfonium ylides with 2-mercaptoindole-3-carbaldehydes and 2-mercaptobenzaldehydes to access thieno[2, 3-b]indoles and benzothiophenes. Issue 16 (31st March 2021) - Yang, Lei; Zhou, Shun; Zhao, Jian-Qiang; You, Yong; Wang, Zhen-Hua; Zhou, Ming-Qiang; Yuan, Wei-Cheng
Abstract : An efficient cascade deprotonation/intramolecular aldol reaction of  α -carbonyl sulfonium ylides with 2-mercaptoindole-3-carbaldehydes and 2-mercaptobenzaldehyde was developed for the synthesis of thieno[2, 3- b ]indoles and benzothiophenes. Abstract : The first catalyst-free cascade deprotonation/intramolecular aldol reaction of α-carbonyl sulfonium ylides with 2-mercaptoindole-3-carbaldehydes and 2-mercaptobenzaldehydes was developed. A series of thieno[2, 3- b ]indoles and benzothiophenes were smoothly obtained in high to excellent yields. The salient features of the protocol include catalyst-free conditions, an environment-friendly solvent, broad substrate scope, and large-scale synthesis.